IMPROVING PROGRAMMING TEACHING METHODOLOGY USING ARTIFICIAL INTELLIGENCE AND ITS APPLICATION IN EDUCATION (Multidisciplinary Journal of Science and Technology, 2026)
In this article, I explore the possibilities of improving programming teaching methodology through the use of artificial intelligence technologies. I analyze AI-based learning tools, interactive educational platforms, and automated assessment systems and their impact on learning effectiveness. I also focus on personalized learning, increasing student engagement, and developing independent thinking skills. The findings show that artificial intelligence can make programming education more efficient, flexible, and learner-centered.